Dehydrative Cross-Coupling of 1-Phenylethanol Catalysed by Palladium Nanoparticles Formed in situ Under Acidic Conditions - Camp, Jason E.; Bousfield, Thomas W.; Dunsford, Jay J.; Adams, James; Britton, Joshua; Fay, Michael W.; Angelis-Dimakis, Athanasios (Synthesis, 2018)
A dehydrative cross-coupling of 1-phenylethanol catalysed by sugar derived, in situ formed palladium(0) nanoparticles under acidic conditions is realised. The acidic conditions allow for use of alcohols as a feedstock in metal-mediated coupling reactions via their in situ dehydration and subsequent cross-coupling. Extensive analysis of the size and morphology of the palladium nanoparticles formed in situ showed that the zero-valent metal was surrounded by hydrophilic hydroxyl groups. EDX-TEM imaging studies using a prototype silicon drift detector provided insight into the problematic role of molecular oxygen in the system. This increased understanding of the catalyst deactivation allowed for the development of the cross-coupling methodology. A 250-12,000 fold increase in molar efficiency was observed when compared to related two-step protocols that use alternative feedstocks for the palladium-mediated synthesis of stilbenes. This work opens up a new research area in which the active catalyst is formed, stabilised and regenerated by a renewable sugar.
Keywords: glucose; nanoparticles; catalysis; dehydrative heck; palladium